Party based Euroscepticism and EU domestic coordination: longitudinal analysis of central and eastern countries. Issue 4 (2nd October 2018) - Kaniok, Petr; Galušková, Johana
ABSTRACT: This article is concerned with the positions of political actors on European Union (EU) issues and examines how these positions impact the coordination of the European agenda. Theoretically, the analysis is based on a model in which political actors maximise their preferences, as developed in rational-choice institutionalism. The authors use two dependent variables: "form of coordination", which denotes the centralisation or decentralisation of systems; and "centre of coordination", which indicates the location within government of the main coordinating body. They seek to explain: 1) party Euroscepticism and the degree of salience governments assign to their European agenda; and 2) other factors including party system fragmentation and political system decentralisation. The findings confirm the premise that party Euroscepticism and the salience of EU issues lead to the centralisation of coordination mechanisms. By contrast, the study refutes the hypothesis that the European agenda is externalised to the ministry of foreign affairs if the cabinet is a Eurosceptic one.